Understory Vegetative Diversity of Post-Thinned Pine Plantations Treated with Fertilizer, Fire and Herbicide in East Texas - Brian P. Oswald; Betsy Ott; Hans M. Williams; Kenneth W. Farrish; James E. Van Kley (International Journal of Forestry Research)
This study assessed biodiversity in the understory of two pine plantations where different management tools (fertilizer, prescribed burning, and herbicide application) were utilized. During three growing seasons, species, percent cover, and number of individuals, and physical characteristics were recorded. Responses to treatment were examined based on comparison of species richness, evenness, diversity, and importance. Two years after treatment, fertilized plots showed a decline in species richness, evenness, and diversity. Prescribed burning and herbicide treatments increased species richness but decreased species evenness, resulting in no change in diversity index. Herbicide treatment reduced the importance of dominant shrubs and increased the importance of disturbance-adapted species.